HARMONISASI EKONOMI BIRU DAN EKOWISATA BERKELANJUTAN DALAM PENGELOLAAN KEGIATAN PARIWISATA DI KAWASAN KONSERVASI TAMAN NASIONAL KARIMUNJAWA - Wishnu Adisatya Dharma; Vincentio Joshua (Faculty of Law, Parahyangan Catholic University, 2026)
Marine ecotourism in Karimunjawa National Park (KNP) possesses considerable potential to promote regional economic development in Jepara Regency and support Indonesia’s Blue Economy agenda. However, the governance of marine ecotourism in KNP is confronted with significant challenges arising from regulatory disharmony between marine conservation objectives and tourism development policies oriented toward economic growth. Increasing tourist arrivals that exceed the ecological carrying capacity of the area have further intensified conflicts over the utilization and management of marine space, contributing to environmental degradation and threatening the sustainability of local communities’ livelihoods. This research aims to examine the regulatory inconsistencies affecting marine ecotourism governance in KNP and to assess their implications for marine conservation and sustainable development. using a normative juridical method complemented by an analysis of field conditions in KNP. It analyzes relevant legislation, development policies of the National Development Planning Agency, and regulations issued by the Minister of Marine Affairs and Fisheries concerning marine conservation governance and tourism management. The findings reveal that the existing regulatory framework has not adequately integrated marine conservation principles, ecological carrying capacity, and the interests of local communities into marine ecotourism policies. Therefore, cross-sectoral regulatory harmonization, the establishment of scientifically informed carrying-capacity limits, strengthened institutional coordination and oversight mechanisms, and the implementation of Blue Economy principles are recommended to ensure ecological sustainability and equitable benefits for coastal communities in KNP.